Malignant risk of indeterminate pediatric thyroid nodules—An institutional experience. Issue 10 (28th June 2019) - Heider, Amer; Arnold, Stacy; Lew, Madelyn; Pang, Judy; Rabah, Raja; Bruch, Steven; Thomas, Inas; Menon, Ram; Cantley, Richard; Davenport, Robertson; Jing, Xin
Abstract: Background: Few studies focus on pediatric thyroid nodules categorized under indeterminate diagnostic categories. The current study was conducted to assess the risk of malignancy of indeterminate pediatric thyroid nodules. Methods: A search of the institutional electronic pathology database from 01/2011 to 09/2018 was performed to identify pediatric (<21 years old) thyroid nodules that were interpreted as follicular lesion of undetermined significance (FLUS), suspicious for follicular neoplasm (SFN), or suspicious for malignancy (SFM) and subsequently managed with surgery, repeat fine‐needle aspiration (FNA), or ≥ 6 months of clinical/imaging monitoring. Results of follow‐up (F/U) surgical resections and repeat FNA/Afirma tests, and clinical and radiologic data were collected. Results: We identified 46 cases from 42 patients (11‐20 years old, 33 females and 9 males), including 30 FLUS, 10 SFN, and 6 SFM. Twenty‐five FLUS, ten SFN, and six SFM cases underwent surgery. The histology revealed carcinomas in 36% of FLUS, 20% of SFN, and 100% of SFM categories; follicular adenomas in 32% of FLUS and 80% of SFN categories; and benign nodules in 32% of FLUS category. All five nonsurgically treated FLUS cases were considered benign based on the findings of repeat FNA/Afirma tests ( n = 3, 3‐22 months F/U) or clinical/radiologic exams ( n = 2, 8‐12 months F/U). Conclusions: Based on a limited study cohort, malignancy was identified in 36%, 20%, and 100% of surgically managed pediatric thyroid nodules categorized as FLUS, SFN, and SFM, respectively; suggesting a markedly higher malignant rate than the implied malignant risk for FLUS and SFM categories in adults.